Disruption to Education During COVID-19: School Nonacademic Factors Are Associated with Children's Mental Health. Issue 2 (16th February 2023) - Tsujimoto, Kimberley C.; Cost, Katherine Tombeau; Laforge-Mackenzie, Kaitlyn; Anagnostou, Evdokia; Birken, Catherine S; Charach, Alice; Monga, Suneeta; Kelley, Elizabeth; Nicolson, Rob; Georgiadis, Stelios; Lee, Nicole; Osokin, Konstantin; et al.
Abstract : This article has supplementary material on the web site: www.jdbp.org . Abstract: Objective: Few studies have examined aspects of the school environment, beyond modality, as contributors to child and youth mental health during the coronavirus pandemic. We investigated associations between nonacademic school experiences and children's mental health. Methods: Parents of children ages 6 to 18 years completed online surveys about school experiences (November 2020) and mental health (February/March 2021). Parent-reported and child-reported school experiences (i.e., nonacademic factors) included school importance, adapting to public health measures, and school connectedness. Children's mental health symptoms of depression, anxiety, inattention, and hyperactivity were collected using standardized parent-reported measures. Results: Children's (N = 1052) self-reported and parent-reported nonacademic factors were associated with mental health outcomes, after adjusting for demographics and previous mental health. Lower importance, worse adapting to school changes, and less school connectedness were associated with greater depressive symptoms ( B = −4.68, CI [−6.04, −3.67] to − 8.73 CI [−11.47, 5.99]). Lower importance and worse adapting were associated with greater anxiety symptoms ( B = − 0.83, CI [−1.62, −0.04] to −1.04 CI [−1.60, −0.48]). Lower importance was associated with greater inattention (B = −4.75, CI [−6.60, −2.90] to −6.37, CI [−11.08, −7.50]). Lower importance and worse adapting were associated with greater hyperactivity (B = −1.86, CI [−2.96, −0.77] to −4.71, CI [−5.95, −3.01]). Conclusion: Schools offer learning opportunities that extend beyond curriculum content and are a primary environment where children and youth develop connections with others. These aspects of school, beyond academics, should be recognized as key correlates of child and youth mental health.